Implementation of Student Worksheets Based on Discovery Learning Assisted by PhET Interactive Simulations to Improve Motivation and Cognitive Learning Outcomes - Hajar, Siti; Adeline Silaban; Umi Purnama; Nur Ilmi Shaqinah; Mawardi Jalil Masri; Muhammad Akbar (Universitas Muhammadiyah Makassar, 2026)
Physics learning in schools often remains dominated by conventional methods, resulting in low student motivation and suboptimal cognitive learning outcomes, particularly when abstract concepts are taught without adequate support for practicum. This condition becomes more challenging in schools with limited laboratory facilities. This study aimed to examine the implementation of discovery-learning-based student worksheets assisted by PhET Interactive Simulations and to determine their effects on students’ learning motivation and cognitive learning outcomes in physics, particularly in the direct current electricity material. This study employed a quasi-experimental method with a pretest-posttest nonequivalent control group design. The research was conducted at Muhammadiyah Senior High School Jayapura and involved 41 students selected through purposive sampling. The instruments used were a learning motivation questionnaire and pretest-posttest items measuring cognitive learning outcomes. The data were analyzed using descriptive statistics, N-gain, independent-samples t-test, and MANOVA using SPSS 16.0. The results showed that students who learned with discovery-learning-based student worksheets assisted by PhET interactive simulations had higher motivation and better cognitive learning outcomes than those who learned with textbook-based worksheets. The independent-samples t-test showed a significance value of 0.000 < 0.05, indicating a significant difference in learning motivation between the two groups. In addition, the MANOVA yielded a p-value of 0.000 < 0.005, indicating a significant difference in both motivation and cognitive learning outcomes. The novelty of this study lies in the integrated use of discovery-learning-based student worksheets and PhET interactive simulations to simultaneously enhance student motivation and cognitive achievement in physics. In conclusion, this approach is effective in fostering active, interactive, and meaningful learning while also serving as an alternative for schools with limited laboratory resources. This study contributes to physics education by providing empirical evidence that integrating structured worksheets, discovery learning, and virtual simulations can enhance both the quality of instruction and student learning performance.